Giant frontal pyomucocele - Yüce, Salim; Doğan, Mansur; Önder Uysal, İsmail; Dursun, Ayhan; Salk, İsmail; Elif Altuntaş, Emine (ENT Updates, 2012)
Giant mucoceles of the frontal sinus are rare but their recognition is important in the differential diagnosis of proptosis and fronto-orbital lesions. We describe a patient with frontal giant mucocele with intracranial as well as orbit and ethmoid sinus involvement. A 53-year-old male was admitted with headache, right exophthalmos and ophthalmoplegia. Computed tomography and magnetic resonance imaging demonstrated a giant frontal sinus mucocele with extension into the left anterior cranial fossa and orbit. The mucocele was treated with a transcranial and endoscopic transnasal approach.